Tanaman Bakau Api-api Putih (Avicenia marina) Berpotensi Menghambat Mikrob Patogen dan Melindungi Post Larva Udang Windu (THE POTENTIAL OF AVICENNIA MARINA TO INHIBITS PATHOGEN MICROBES AND PROTECTS THE POST LARVA OF TIGER PRAWN) - Saptiani, Gina; Asikin, Andi Noor; Ardhani, Fikri; Hardi, Esti Handayani (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
The research aims to study potency of Avicennia marina leaf extract to inhibit pathogens in vitro and in vivo on post larvae of tiger prawn. The leaves we re chopped, dried and extracted with water solvents, sea water andethanol. In vitro inhibitory tests were performed using agar disc diffusion (ADD) and minimal inhibitory concentration (MIC) methods. The in vivo test on tiger prawn PL-8 was given by submersion, which then tested with Vibrio harveyi and Saprolegnia sp. The in vitro test showed A. marina extract can inhibit V.harveyi and Saprolegnia sp. In vivo tests of V. harveyi and Saprolegnia sp. infections, showed 60- 88% survival and 57.33-86.67%, with protective ability of the highest pathogen infection of 80.80% and 77.80%. The best A. marina extract that can inhibit microbial and protect the tiger prawn from pathogen infection is ethanol extract with concentration 1,250-1,500 ppm, followed by sea water extract 1,500 ppm and water extract 1,500 ppm respectively